2019
DOI: 10.3892/mco.2019.1802
|View full text |Cite
|
Sign up to set email alerts
|

Expression of keratin 15 in dentigerous cyst, odontogenic keratocyst and ameloblastoma

Abstract: The etiology and pathogenesis of odontogenic lesions are poorly understood. Keratin 15 (K15) is a type I cytoskeletal protein that provides structural support to the cells and has been considered to be a stem cell marker. The aim of the present study was to evaluate the expression of K15 in the epithelial lining of dentigerous cysts (DCs), odontogenic keratocysts (OKCs) and ameloblastomas (ABs). The study included 41 samples of DCs (n=13), OKCs (n=12), and AB tissues (n=16). K15 protein expression was evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…A series of studies have shown that rodent incisors grow continuously throughout life owing to the epithelial progenitor cells in the cervical loop, an area where the inner and the outer enamel epithelium meet at the rim of the enamel organ at bell stage (12)(13)(14). Moreover, stem cell markers such as Oct-4, CD44 and K15 have been demonstrated in odontogenic lesions (15,16). Evidences above suggest the possibility that there are stem cells in the capsule of DC.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies have shown that rodent incisors grow continuously throughout life owing to the epithelial progenitor cells in the cervical loop, an area where the inner and the outer enamel epithelium meet at the rim of the enamel organ at bell stage (12)(13)(14). Moreover, stem cell markers such as Oct-4, CD44 and K15 have been demonstrated in odontogenic lesions (15,16). Evidences above suggest the possibility that there are stem cells in the capsule of DC.…”
Section: Introductionmentioning
confidence: 99%
“…However, knowledge is little about the expression of K15 in odontogenic cysts and tumors. We have previously investigated the expression of K15 in dentigerous cyst, odontogenic keratocyst, and ameloblastoma ( 16 ). Moreover, the expression of COX-2 and K15 in RCs is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“… 9 The expression of multiple cytokeratins in cysts and odontogenic tumors such as CK5/6, 7, 13, 14, 15, 16, 17, 19, AE1/AE3 has been reported. 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 CK14 is considered to be the main odontogenic epithelium cytokeratin. 7 Currently, the role of amelogenin in aggressiveness of OC and OT is controversial, since some studies find no difference in the expression of amelogenin in benign or malignant OT while other authors associate it with greater cell differentiation and less aggressiveness.…”
Section: Introductionmentioning
confidence: 99%